MicroRNA-26b Regulates the Microglial Inflammatory Response in Hypoxia/Ischemia and Affects the Development of Vascular Cognitive Impairment - Kang, Yuan-Cheng; Zhang, Li; Su, Ying; Li, Yue; Ren, Wen-Lei; Wei, Wen-Shi (Frontiers in Cellular Neuroscience, 2018)
Background: Microglia play an important role in the central nervous system as immune cells and are often activated by post-ischemic injury. MicroRNAs are small endogenous RNAs affecting many complex cellular biological functions that are involved in neurodegenerative and cerebrovascular diseases. Previous studies have shown that microRNA-26b (miR-26b) is downregulated in BV-2 cells exposed to oxygen-glucose deprivation (OGD). Objective: This study aimed to investigate how miR-26b regulates microglial activation and its neurotoxicity as well as the effect of miR-26b on vascular cognitive impairment (VCI). Methods: Here, we used PCR to detect the mRNA expression of miR-26b and cytokines, western blot for the protein expression of cytokines, and the live/dead assay for neuronal apoptosis. In addition, we employed a luciferase assay to identify the possible target genes of miR-26b. Furthermore, we studied the effects of cerebral ischemia by bilateral common carotid artery occlusion (BCCAO) in rats. We used staining to identify neurons and microglia, and we tested cognitive function by the T-maze test. Results: Our results showed that OGD activated microglia and increased the expression of interleukin (IL)-6 and other cytokines. Similarly, BCCAO activated microglia and increased the expression of IL-6 in the hippocampal CA1 area. We further found that miR-26b decreased the number of activated microglia and targeted IL-6. Moreover, miR-26b expression attenuated microglial activation, inflammation, neurotoxicity, and VCI. Conclusion: Our results suggested that miR-26b is involved in microglial activation and neurotoxicity in hypoxia/ischemia via IL-6. Therefore, increasing miR-26b expression may improve cognitive function.